Os números racionais nos anos iniciais do ensino fundamental: investigando saberes docentes - Herika Nunes Torres Fonseca (2008)
This work was developed in the field study of mathematics education and aimed to analyze the knowledge and non-knowledge of rational numbers of teachers of the first years in Elementary Education. The interest in this research was due to the lack of studies in this area which is able to deepen the discussion on the learning and teaching of rational numbers in the first years of schooling. Thus this study investigates how teachers of first grades of Elementary education relate with these numbers throughout their practices; which knowledge guide their practice; how this knowledge was constructed; and what are the difficulties and insecurities faced during the teaching of this content. The theoretical frame is based on the need to understand the teachers modes of knowledge; how the construction of different knowledge takes place, and especially how the knowledge and non-knowledge of rational numbers are formed. Some studies in the areas of education and Mathematical education, especially those done by Tardif (2002), Fiorentini (1998), Shulman (1987), Gauthier et al. (1998), Moreira e David (2005) e Behr et al. (1983), guided the methodological choices in relation to the analysis of data in this study. The research was divided into two phases. Firstly, the investigation aimed at discovering how the relationship of a group of eight teachers with the mathematical schooling was built. This investigation perceived, through oral and written reports, how the interviewees related with Mathematics as students of the early years of Elementary teaching and the following years of study, and as teachers. On the second phase of the research, only three teachers attended weekly meetings, and the goal was to identify the knowledge and non-knowledge that involve their everyday practices with rational numbers, which was done by studying these numbers and by taping some of these teachers classes. The final results showed that the field of mathematical education should rethink the initial and/or continuing education of teachers that teach rational numbers in the first years of Elementary education.